PEMANFAATAN EKSTRAK BIJI KELOR (Moringa oleifera Lamk) DENGAN KULIT ARI SEBAGAI KOAGULAN ZAT WARNA REAKTIF DALAM LARUTAN MODEL LIMBAH CAIR INDUSTRI KAIN BESUREK - Rahma Hidaiyanti (UNIVED Press, Universitas Dehasen Bengkulu, 2016)
The aim of this research was to determine the ability of merunggai seed powder extract with shelled and non-shelled as a natural coagulant to reducing reactive colours concentration in liquid waste model of industrial besurek. In this research, for the first time merunggai seed powder with shelled and non-shelled was extracted with powder percentage variation of 3%, 5% and 7%, while period process of extraction variation were 30 minutes, 45 minutes and 60 minutes at the temperature of extraction 60 oC. Then merunggai seed extract with shelled and non-shelled was used as coagulant to reducing reactive colours concentration in model liquid. The result showed that optimum condition for merunggai seed powder extract with shelled is 5% powder percentage with period process of extraction during 45 minutes for reactive colours blue, red and yellow. The decrease of reactive colour content were 491,63 mg/mL, 490,02 mg/mL and 466,60 mg/mL respectively. Keywords: Moringa oleifera Lamk, coagulation, extraction, reactive colours